Efficient luminomagnetic and conductive Eu and Dy doped ZnO phosphors for multifunctional devices. (August 2020) - Rehani, Divya; Bishnoi, Swati; Saxena, Manish; Haranath, D.; Gupta, Vinay; Sharma, Shailesh Narain
Abstract: In this study, europium (Eu) and dysprosium-(Dy) doped phosphors, i.e., ZnO:Eu, ZnO:Dy, and Eu:Dy co-doped zinc oxide (ZnO:Eu, Dy) semiconductor phosphors, with optimized concentrations, were synthesized using the conventional solid-state reaction method in an oxygen environment. Detailed structural, morphological, and compositional investigations were conducted using X-ray diffraction (XRD), scanning electron microscopy, and energy-dispersive X-ray measurements, respectively. Photoluminescence (PL) emission spectra were recorded under different excitation wavelengths to assess the optical characteristics. Electrical analysis was conducted using an inductance (L), capacitance (C), and resistance (R) (LCR) meter and a Keithley source meter, and magnetic analysis was performed using a vibrating sample magnetometer (VSM). XRD confirmed the presence of Eu and Dy ions because the diffraction peaks matched perfectly with those for Eu2 O3 and Dy2 O3, respectively. The PL results indicated the broad emissions from the samples in the visible region (400–700 nm) under different ultraviolet excitation wavelengths. The VSM results demonstrated that both the Dy-doped and Eu:Dy co-doped ZnO samples exhibited paramagnetic behavior at room temperature, but not the undoped and Eu-doped ZnO samples. The ZnO:Dy sample had superior parameters in terms of the electrical measurements such as the AC/DC conductivity, capacitance, current density, and dielectric constant compared with the ZnO:Eu and ZnO:Eu, Dy samples. These detailed investigations of the optical, magnetic, and electrical properties demonstrate that ZnO:Dy and ZnO:Eu, Dy may be promising materials for use in optical devices. Highlights: ZnO:Eu, Dy shows luminescence. ZnO:Eu, Dy is magnetic & conductive. ZnO:Eu, Dy is luminomagnetic.